Papillary Renal Cell Carcinoma Arising in a Lymph Node Metastasis of a Testicular Teratoma: A Very Rare Occurrence. (August 2016) - Ozturk Sari, Sule; Ozluk, Yasemin; Taskin, Orhun Cig; Polat, Beldan; Ozturk, Ilker; Ekenel, Meltem; Kilicaslan, Isin; Bilgic, Bilge
We present a case of a teratoma with somatic type malignancy (TSM) in the form of papillary renal cell carcinoma (pRCC) within supraclavicular and retroperitoneal lymph node metastases of a testicular pure teratoma. Resection of both masses revealed a teratoma without any other germ cell tumor component. A papillary carcinoma component was also detected intermingled with the teratomatous elements. The carcinoma cells displayed eosinophilic cytoplasm and prominent nucleoli. Groups of foamy histiocytes in the fibrovascular cores was a striking finding that brought pRCC to mind. Immunoreactivity for CK7, PAX8, AMACR, CD10, napsin, and vimentin along with morphologic findings confirmed renal cell differentiation. No radiological evidence of a primary renal cell carcinoma was found in the kidney. Consequently, pRCC arising in a teratoma was diagnosed. TSM is described as teratoma with a malignant component that is typically encountered in other organs and tissues. TSM in the form of pRCC is an extremely rare entity. Our case is the second example of a testicular germ cell tumor metastasis with a somatic malignancy in the form of pRCC. In conclusion, carcinomas of renal cell differentiation should be kept in mind as a rare form of TSM, especially in metastatic germ cell tumors.